1995
DOI: 10.1108/09578239510098518
|View full text |Cite
|
Sign up to set email alerts
|

Mentoring for new headteachers: recent British experience

Abstract: Reports selected findings from a national evaluation of a British pilot scheme for mentoring new primary and secondary headteachers. Information was collected by questionnaire from 238 new headteachers, from 303 experienced headteachers who acted as mentors and via 16 detailed case studies of reportedly successful pairs. Deals with the nature and impact of the mentoring process and the characterisitics of successful mentoring. Mentoring was judged to be a success by the overwhelming majority of participants be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0
5

Year Published

1996
1996
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(69 citation statements)
references
References 4 publications
3
61
0
5
Order By: Relevance
“…According to the findings from the research undertaken by Bolam et al (1993), professional working relationships are concerned with the following aspects, which are underlined, together with my commentary afterwards.…”
Section: Professional Working Relationshipsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the findings from the research undertaken by Bolam et al (1993), professional working relationships are concerned with the following aspects, which are underlined, together with my commentary afterwards.…”
Section: Professional Working Relationshipsmentioning
confidence: 99%
“…A model to provide the context for the HoD role is conceptualised in Figure 1, which is based on a revised version of the one proposed by Bolam et al (1993) identification of characteristic management processes and structures in schools, which the staff themselves had perceived as being effectively managed. In all, a total of 57 schools from the primary and secondary sectors volunteered to participate in the study.…”
Section: A Model Of the Head Of Department's Role In Effective Schoolmentioning
confidence: 99%
“…Dogm atic advocacy of any one particular m odel would seem to be less than desirable, not least since there are likely to be com peting perspectives abou t what m akes m anage m ent developm ent effective and fashions do change (Thody, 1992). There is no overlooking the signi® cant in¯uence which the policy context has had on the practice of educational m anagem ent developm ent in the U K and elsewh ere, but one of the problem s is that all too frequently, policy is form ulated and implemented in an ad hoc and increm ental fashion (Bolam , 1995). Ensuring greater coherency m ay require som e sort of national fram ework for educational m anagem ent developm ent, a point m ade forcibly in discussions concerning LD C s (e.g.…”
Section: Education Al M Anagem Ent D Evelopm Entð An Overviewmentioning
confidence: 97%
“…Governors' eOE ectiveness was not highly rated. In school eOE ectiveness studies, governors were conspicuous by their absence (Bolam et al, 1993;Cheng, 1993;Mortimore, 1988). A 1992 survey found that governors had minimal in¯uence on curriculum policy in two-thirds of primary schools and 60% of secondary schools.…”
Section: Current Statusmentioning
confidence: 99%